Strategi Pengamanan Wilayah Oleh Skuadron Udara 51 UAV - Muhammad Nurdi Iriansyah; Heri Casnoto; Yusa Djuyandi (Akademi Angkatan Udara, 2021)
The security of Indonesia's territorial territory requires a breakthrough in terms of regional security strategies. This is due to the limitation of resources owned by the government compared to the area for which it is responsible. Advances in science and technology in the use of Unmanned Aerial Vehicles (UAVs) have provided breakthroughs as a solution in regional security strategies more effectively and efficiently without compromising the quality of regional security. The Air Force through the 51 UAVs Air Squadron, as an air squadron that relies on the use of UAVs, has proven that the use of UAVs is capable of making a real contribution to the security strategy of the region. This is evidenced by the involvement of the 51 UAV Air Squadron in several operations that provide optimal results in terms of surveillance of the intended object. With reference to the advantages possessed by the 51 UAV Air Squadron, it can be concluded that the role of UAVs in the strategy of securing the region is significant. As a follow-up, efforts are needed to increase the breadth of UAV range and use surveillance results more widely with cross-institutional that can be expanded so that its use can be maximized.